2015
DOI: 10.1039/c5nj00343a
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic degradation of 2,4,4′-trichlorobiphenyl into long-chain alkanes using Ag nanoparticle decorated flower-like ZnO microspheres

Abstract: Toxic 2,4,4 0 -trichlorobiphenyl (PCB28) was photocatalytically degraded by the action of Ag nanoparticle decorated nanosheet-assembled ZnO microspheres via a new photocatalytic degradation pathway. The outright degradation into long-chain alkanes via ring-opening reactions was demonstrated by gas chromatography-mass spectrometry. ExperimentalThe preparation of Ag-NPs@ZnOmsThe detailed fabrication was reported in our previous report. 20 Briefly, zinc acetate dihydrate (2.5 mmol) and sodium citrate † Electronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Ansari et al synthesized 1 and 3 % Ag@ZnO nanocomposites via a gel combustion route, and observed the photodegradation of methylene blue (MB) [32]. Very toxic PCB (2,4,4′-trichlorobiphenyl, PCB28) was degraded photocatalytically using Ag/ZnO microspheres under UV light irradiation [22]. Kuriakose et al deposited Ag on ZnO nanospindles using a citrate-assisted photo-reduction method and tested them on photocatalytic MO degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Ansari et al synthesized 1 and 3 % Ag@ZnO nanocomposites via a gel combustion route, and observed the photodegradation of methylene blue (MB) [32]. Very toxic PCB (2,4,4′-trichlorobiphenyl, PCB28) was degraded photocatalytically using Ag/ZnO microspheres under UV light irradiation [22]. Kuriakose et al deposited Ag on ZnO nanospindles using a citrate-assisted photo-reduction method and tested them on photocatalytic MO degradation.…”
Section: Introductionmentioning
confidence: 99%
“…In another study by Deng [ 27 ], found tetradecane and pentadecane as product during photocatalytic degradation of 2,4,4-TCB. Comparing results of present study with, Deng [ 27 ], tetradecane 1-chloro only one similar compound was found. Other compound, nona, hexa, hepta and octadecane 1-chloro was not found in study by Dung.…”
Section: Resultsmentioning
confidence: 99%
“…However, it's necessary to mention that, for the 3D Ag-NPs/ZnO nanorod hybrid substrate, photocatalytic degradation of PCB77 may happen based on the previous research. 202 Intermediate products, which have similar chemical structures but higher affinity to the SERS substrate, could cause interference. Capture of analytes with surface-functionalized SERS substrates.-When analytes cannot be directly absorbed on a bare SERS substrate, surface functionalization is performed on the SERS substrate surface.…”
Section: -180mentioning
confidence: 99%